No association between vitamin D and atopy, asthma, lung function or atopic dermatitis: a prospective study in adults. Issue 11 (19th August 2015) - Thuesen, B. H.; Heede, N. G.; Tang, L.; Skaaby, T.; Thyssen, J. P.; Friedrich, N.; Linneberg, A.
Abstract Studies suggest that vitamin D may be involved in the pathogenesis of allergic disorders, asthma and decreased lung function. However, results are inconsistent and only few prospective studies have examined adults. The purpose of this study was to investigate the association of serum 25‐hydroxy vitamin D (s25(OH)D) with atopy, atopic dermatitis (AD), asthma, wheezing and impaired lung function in a prospective study of Danish adults. A random sample of 3471 persons was examined in 2006–2008. Of these, 2308 were re‐examined 5 years later. s25(OH)D and specific IgE against four common inhalant allergens were measured by standard procedures. Wheezing, asthma and AD were assessed from questionnaires and lung function was measured by spirometry. We found no statistically significant associations between s25(OH)D and prevalence or incidence of atopy, AD, asthma or wheezing. Associations with lung function were inconsistent. We conclude that vitamin D status does not influence these conditions in adults.